PERAN HUMAS PEMBENTUK OPINI PUBLIK DALAM UPAYA PENCITRAAN LEMBAGA PENDIDIKAN - Patrea Reola Pramungkas (Institut Agama Islam Negeri (IAIN) Palopo, 2020)
The existence of public relations management is very important in an educational institution, especially in communication with the community to form a good opinion. Education is the biggest source of investment in developing and making people whole (insanul kamil). Understanding someone's opinion, in this case public opinion is not easy. Because it is the formation of public opinion formed by the selective public, because in all problems there is always every public. Public Relations plays a very important role in every institution or institution, because public relations is one of the strategic ways in creating a positive or negative image in an institution. In this case public relations has a broad relationship, and the role of public relations in the development of education has a very urgent position, especially in determining the direction of education in accordance with the wishes of all parties, especially customer demands. The development of public opinion with a variety of characters increasingly diverse, both internal and external requires special solutions in communicating with them. Organizational communication activities are strategic communication activities that need to be carried out by the organization. Because this is related to the image of the educational institution itself.